Massilia Virus, A Novel Phlebovirus (Bunyaviridae) Isolated from Sandflies in the Mediterranean - Charrel, Rémi N. (Mary Ann Liebert, Inc., 2009)
A new virus was isolated from three independent pools of Phlebotomus perniciosus sandflies (Diptera; Psychodidae) trapped in two regions of southeastern France, located 90 miles apart. Microscopic, antigenic and genetic analyses indicate that this novel virus belongs to the genus Phlebovirus in the family Bunyaviridae. The new virus is designated Massilia virus since the first isolate was obtained from sandflies collected in the suburban area of Marseille. The complete genome sequence was determined and used to compare the genetic and phylogenetic relationships of Massilia virus with other phleboviruses. Genetic and antigenic properties were employed to address whether or not Massilia virus should be considered a new species within the genus, or a member of a previously recognized species. Cerebrospinal fluid specimens, collected from local patients with central nervous system infections during the previous four-year period were tested for the presence of Massilia virus RNA, but gave negative results. In conclusion, Massilia virus is proposed as a member of the Sand-fly fever Naples virus complex; its public health importance has yet to be determined.